The Management of Ruptured Cerebral Aneurysms: Life After ISAT. Issue 1 (1st February 2005) - Sellar, Robin
Abstract : BACKGROUND Aneurysmal subarachnoid haemorrhage (SAH) is devastating for many young and middle aged patients. Mortality and disability have altered little over the past 20 years (Hop et al . 1997). Moreover, about one-quarter of patients do not even survive long enough to reach hospital. Of those that do, about one-third rebleed in the first three weeks with a subsequent mortality of 60–80% (Alvord et al . 1972; Kassell et al . 1990; Brilstra et al . 2000; Roos et al . 2000). The first concern after resuscitation is therefore to secure the aneurysm, and so prevent rebleeding. This also allows more aggressive treatment of the complications of SAH such as vasospasm. Since Dandy first surgically clipped an aneurysm in the 1930s, clipping has until recently been the accepted method of isolating the aneurysm from the parent artery. Although clipping was never subjected to a randomised trial, it has been calculated that it reduces the mortality